Managing Director's Global Policy Agenda. (Policy Papers; Policy Paper ;, 2012)
The global recovery has suffered new setbacks with uncertainty weighing heavily on confidence and prospects. Output is contracting in the euro area and growth has decelerated in many other advanced economies and major emerging markets. Markets have been buoyed by central bank action in the advanced economies which provides an opportunity to lay the basis for a recovery. Policymakers must detail, and aggressively implement, measures to address the underlying weaknesses-fiscal, financial, and structural. In the Euro area the ESM and the OMT need to be deployed, banking union advanced, and national authorities should implement strong policies to credibly ensure fiscal consolidation over the medium-term and to raise growth and employment. In the U.S., the immediate priority is to resolve the fiscal cliff and raise the debt ceiling, while developing an appropriately ambitious medium-term fiscal consolidation plan. In the Euro area, the Fund will support members' efforts by assisting in the development and monitoring of well-designed adjustment programs and providing analysis and advice on options for banking and fiscal union. For other advanced economies, the Fund will assess the implications of the underlying policy framework.